2021
DOI: 10.31703/gsr.2021(vi-i).10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perceived Quality of Home Environment and Self-Concept of Students at Undergraduate Level

Abstract: The objective of the study was to identify the relationship of different dimensions of perceived quality of home environment and self-concept of undergraduate university students. Correlational research was selected as the research design. The population of the study was university students of the education department of public and private universities of Lahore. The total population was 1760. A proportionate stratified random sampling technique was used to select the sample. The strata were formed on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Similar results have been highlighted in other studies, such as those reported by Kaur et al [59], indicating a positive correlation between a supportive family environment, security, and a positive self-concept. Additionally, Kashif et al [60] found a significant relationship between good home quality, secure attachment, and a positive self-concept, while Maunder and Hunter [22] reported similar findings. According to Torres and Rodrigo [61], there exists a link between attachment and self-concept, both being important and fundamental dimensions in predicting the psychological wellbeing of children and adolescents, thus reinforcing the existing evidence between these two constructs.…”
Section: Discussionmentioning
confidence: 88%
“…Similar results have been highlighted in other studies, such as those reported by Kaur et al [59], indicating a positive correlation between a supportive family environment, security, and a positive self-concept. Additionally, Kashif et al [60] found a significant relationship between good home quality, secure attachment, and a positive self-concept, while Maunder and Hunter [22] reported similar findings. According to Torres and Rodrigo [61], there exists a link between attachment and self-concept, both being important and fundamental dimensions in predicting the psychological wellbeing of children and adolescents, thus reinforcing the existing evidence between these two constructs.…”
Section: Discussionmentioning
confidence: 88%